Distinct pathways in the pathogenesis of sebaceous carcinomas implicated by differentially expressed MicroRNAs - Michael T. Tetzlaff (2018)
Copyright 2015 American Medical Association. All rights reserved. IMPORTANCE The molecular-genetic alterations contributing to the pathogenesis of sebaceous carcinoma and sebaceous adenoma remain poorly understood. Given that sebaceous carcinoma is associated with substantial morbidity and mortality, there is a critical need to delineate the pathways driving sebaceous carcinoma and candidate molecules for targeted therapy. OBJECTIVE To describe differentially expressed microRNAs (miRNAs) in a series of periocular sebaceous carcinomas compared with sebaceous adenomas in order to identify pathways driving the pathogenesis of sebaceous carcinoma. DESIGN, SETTING, AND PARTICIPANTS Thirty sebaceous carcinomas and 23 sebaceous adenomas (including 11 that were confirmed to be related to Muir-Torre syndrome and 6 that were confirmed to be sporadic) were obtained from archives (from 48 patients) of 2 institutions (University of Texas MD Anderson Cancer Center, Houston, and Siriraj Hospital, Mahidol University, Bangkok, Thailand) and profiled. MAIN OUTCOMES AND MEASURES Expression of miRNAswas determined using total RNA from formalin-fixed, paraffin-embedded tissue and real-time reverse transcription-polymerase chain reaction performed in a microfluidics card containing 378 unique miRNAs. Fold change was determined using the Ct method (reference probe, RNU48). Median centering was used to normalize the data. Two-sample t tests were used to identify differentially expressed miRNAs. The false discovery rate was assessed by β-uniform mixture analysis of P values from the t statistics. Significance was defined by this estimated false discovery rate. RESULTS Serial testing and validation confirmed overexpression of 2 miRNAs previously reported to be oncogenic, miR-486-5p (4.4-fold; P = 2.4 × 10-8) and miR-184 (3.5-fold; P = 1.7 × 10-6), in sebaceous carcinoma compared with sebaceous adenoma and downregulation of 2 miRNAs previously reported to have tumor-suppressive properties, miR-211 (-5.8-fold; P = 2.3 × 10-9) and miR-518d (-4.5-fold; 6.7 × 10-5), in sebaceous carcinoma compared with sebaceous adenoma. CONCLUSIONS AND RELEVANCE Sebaceous carcinoma exhibits an miRNA expression profile distinct from that of sebaceous adenoma, implicating dysregulation of NF-κB and PTEN (targets of miR-486-5p) and TGF-β signaling (target of miR-211) in the pathogenesis of sebaceous carcinoma. The identification of miRNAs whose expression is altered in sebaceous carcinoma compared with sebaceous adenoma provides a novel entry point for a more comprehensive understanding of the molecular-genetic alterations pivotal to the development of sebaceous carcinoma.